An ethnomedicinal survey of medicinal plants from a sacred forest of Western Odisha, India. - Antaryami Pradhan; Satyendra Prasad Mishra; Niranjan Behera (International Journal of Phytomedicine, 2016)
Sacred forests are being protected by means of cultural and religious beliefs by the local communities and act as people participatory conservation sites for several important medicinal plants. Sacred forests are one of the oldest forms of biodiversity conservation sites still effectively managed by local people and act as in-situ conservation sites. In this context, the present study was carried out in Andhari sacred forest of Jharsuguda district as to collect the information regarding the traditional ethno medicinal knowledge acquired by the local medical practitioners. Only few indigenous people have adequate knowledge regarding the medicinal plants and their uses. These traditional knowledge were rapidly degrading and if not documented will be lost forever. The present study reveals the presence of 91 plants species belonging to 46 families being used by the practitioners to treat various diseases like dysentery, diarrhea, indigestion, worm infection, wound healing, headache, stomach disorders, Rheumatic disorders, snake bite, poisonous bite, menstrual problem etc. This ethnomedicinal information further needs to be validated by clinical trials for their safe uses. The study also reported the existence of 8 RET (Rare, Endangered and Threatened) medicinally important species which makes this site a biological hotspot and needs further effective conservation efforts.